2015
DOI: 10.14453/aabfj.v9i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social and Environmental Responsibility in an Emerging Economy: Through the Lens of Legitimacy Theory

Abstract: Efforts to promote Corporate Social and Environmental Responsibility (CSER) require an understanding of stakeholder attitudes toward enhanced responsibility. However, little is known about current attitudes on this subject, or the determinants of these attitudes. This study presents a survey of the attitudes of Indian managers, toward 18 social and 16 key contemporary environmental management issues. The findings indicate that respondents are concerned about a range of issues surrounding social responsibility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
(69 reference statements)
0
8
0
1
Order By: Relevance
“…Finally, the organisation can attempt, again through communication, to become identified with symbols, values or institutions which have a strong base of social legitimacy. However, Bhattacharyya (2015) suggests that organisational legitimacy is not a universal concept, and that whether an organisation and its actions are perceived as legitimate is socially created, and therefore subject to change in the social environment in which the organisation operates.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Finally, the organisation can attempt, again through communication, to become identified with symbols, values or institutions which have a strong base of social legitimacy. However, Bhattacharyya (2015) suggests that organisational legitimacy is not a universal concept, and that whether an organisation and its actions are perceived as legitimate is socially created, and therefore subject to change in the social environment in which the organisation operates.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The information provided by firms should be thorough and adequate for CSR to be considered as a purchase criterion. Efforts to promote CSR activities involve a thorough understanding of stakeholder attitudes toward CSR activities (Bhattacharyya, 2015). In this case, there were consumers who were willing to purchase from a responsible firm, provided they had enough information:…”
Section: Resultsmentioning
confidence: 99%
“…That is, some studies have claimed that it pays to be green and at the same time, other studies have observed that it does not pay to be green. Bhattacharyya (2015) in his paper argues that India, although enjoying a high economic growth rate similar to other BRIC and emerging economies, is not doing enough in terms of its responsibility with respect to sustainable development. Like many other emerging economies, India is also highly vocal against adopting regulatory measures to contribute to sustainable development citing the negative financial impacts of such measures in its corporate and business sectors.…”
Section: Editorial Volume 9 Issue 2 Monir Mirmentioning
confidence: 99%
“…Like many other emerging economies, India is also highly vocal against adopting regulatory measures to contribute to sustainable development citing the negative financial impacts of such measures in its corporate and business sectors. However, Bhattacharyya (2015) provides evidence that the Indian corporate sector will welcome mandatory corporate social responsibility reporting which indicates that Indian regulators should not be shying away from implementing stringent regulations promoting the sustainable development of India.…”
Section: Editorial Volume 9 Issue 2 Monir Mirmentioning
confidence: 99%